PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA DAN QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI SMKN - Ahmat, Nurul; Jennah, Rodhatul; Gofur, Abdul (Jurnal Muara Pendidikan, 2025)
Lack of student motivation in learning Islamic Religious Education (PAI) is one of the challenges faced by teachers in the classroom. This study aims to develop learning media based on Canva and Quizizz to increase student motivation in learning the subject of Islamic Religious Education (PAI) for grade XI TKJ at SMKN 8 Palangka Raya. The research method used is Research and Development (R&D) with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation The Analysis stage identifies the needs of students and teachers for interactive media. In the Design stage, a media prototype is designed using Canva for attractive visual presentations and Quizizz for game-based evaluation. The Development stage involved expert validators for media, content, questions, and learning motivation questionnaires before testing. Expert validator results showed an average percentage of 91.47%, and evaluation results indicated that this media effectively increased student participation and enthusiasm, with learning motivation percentages rising from 49.8% (pre-intervention) to 84.6% post-intervention. These findings prove that the integration of Canva and Quizizz can be an innovative solution in PAI learning, while also offering an adaptive media development model for educators. This study recommends the use of gamification-based digital technology for other subjects to create more interactive and enjoyable learning experiences.